Transformation of political campaigning in the digital era: The impact of social media and digital communication - Dharta, Firdaus Yuni; Ghazalie, Ghazalie; Putra, Doly Andhika; Albrecht, Malte (Universitas Negeri Malang, 2025)
The digital era has brought about a revolution in various aspects of life, including the realm of political campaigning. This study examines the transformation of political campaign strategies in the context of the influence of social media and digital communication. Utilizing a qualitative approach, this research investigates how digital platforms and social media have impacted campaign approaches, altered the interaction dynamics between candidates and voters, and influenced voter behaviour. The findings indicate that social media is central to informing, engaging, and mobilizing the masses, especially among the younger generation. Moreover, digital communication allows for more personalized, real-time, and data-oriented campaigns. However, the potential for disinformation and polarization also increases with the presence of social media as a campaign medium. This study provides insights into the importance of adapting political campaign strategies in the digital era and the necessity for a balanced approach between utilizing technology and considering ethics in communication.